Lyman Bryson papers - Bryson, Lyman, 1888-1959.
Correspondence, diaries, memoranda, articles, lectures, writings, transcripts of broadcasts, subject files, business and financial records, biographical material, appointment books, newspaper clippings, and other papers documenting Bryson's public relations work for the American National Red Cross and the League of Red Cross Societies following World War I and directorship of American Junior Red Cross programs; subsequent work in adult education through his association with Columbia University; and his role in developing educational radio and television programs for the Columbia Broadcasting System. Includes material on Department X, a committee organized by Bryson at the request of CBS president William S. Paley to examine issues relating to global changes in politics, economics, science, technology, public opinion, and social and government policy in the future. Includes an account of Bryson's interview with H.G. Wells in 1920; drafts of novels, short stories, books, plays, and poems; and material relating to public communication, philosophy, and his travels in Asia, Europe, and the Middle East.
Correspondents include Bower Aly, Edmund de S. Brunner, George T. Bye, Morse A. Cartwright, James Mitchell Clarke, Mary L. Ely, Louis Finkelstein, Sir Claude H. Hill, Anne E.M. Jackson, Robert E. Olds, William S. Paley, and David Riesman.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Radio and television broadcaster, author, and educator. Full name: Lyman Lloyd Bryson.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aly, Bower, -- 1903- -- Correspondence; Brunner, Edmund de S. -- 1889-1973 -- Correspondence; Bye, George T. -- Correspondence; Cartwright, Morse A. -- 1890- -- Correspondence; Clarke, James Mitchell -- Correspondence; Ely, Mary L. -- Correspondence; Finkelstein, Louis, -- 1895-1991 -- Correspondence; Hill, Claude H. -- Sir, -- 1866- -- Correspondence; Hill, Claude E. -- 1874-1957 -- Correspondence; Jackson, Anne E. M. -- Correspondence; Olds, Robert Edwin, -- 1875-1932 -- Correspondence; Paley, William S. -- 1901-1990 -- Correspondence; Riesman, David, -- 1909-2002 -- Correspondence; Wells, H. G. -- 1866-1946.; American Junior Red Cross; American National Red Cross; Columbia Broadcasting System, inc; Columbia University; League of Red Cross Societies; Adult education; Communication; Philosophy; Public opinion; Radio in education -- United States; Radio programs; Science -- History -- 20th century; Social policy; Technology; Television in education -- United States; Television programs; World economics -- 20th century; World politics -- 20th century; Asia -- Description and travel; Europe -- Description and travel; Middle East -- Description and travel; Authors; Broadcasters; Educators